INSTITUTIONAL SUPPORT FOR THE TECHNOLOGICAL AND SCIENTIFICAL RESEARCH IN PERU - García Z., Teonila (2004)
This work proposes an institutional strengthening of organizations encouraging technological and scientifical research, with the purpose of stating a government policy on Science and Technology development, one able to boost investment and provide with productivity growing in enterprises, in order to guarantee goods and services competitiveness, and improve peruvian population living conditions both in the long and short run.